2015
DOI: 10.2147/copd.s74315
|View full text |Cite
|
Sign up to set email alerts
|

Continuing to Confront COPD International Surveys: comparison of patient and physician perceptions about COPD risk and management

Abstract: PurposeUsing data from the Continuing to Confront COPD International Physician and Patient Surveys, this paper describes physicians’ attitudes and beliefs regarding chronic obstructive pulmonary disease (COPD) prognosis, and compares physician and patient perceptions with respect to COPD.MethodsIn 12 countries worldwide, 4,343 patients with COPD were identified through systematic screening of population samples, and 1,307 physicians who regularly saw patients with COPD were sampled from in-country professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…However, one-third of the smokers in our study disagreed that COPD to a great extent is caused by exposing one-self to risk factors indicating a great lack of knowledge of the main aetiology of COPD. This is supported by the study by Menezes et al [24] reporting that 31% of a cohort of 4343 patients with COPD somewhat disagreed/strongly disagreed that smoking is the cause of most cases of COPD. We found that the smokers feared COPD more than the ex- and never-smokers, but the figures were however low (5.1 vs .…”
Section: Discussionsupporting
confidence: 52%
“…However, one-third of the smokers in our study disagreed that COPD to a great extent is caused by exposing one-self to risk factors indicating a great lack of knowledge of the main aetiology of COPD. This is supported by the study by Menezes et al [24] reporting that 31% of a cohort of 4343 patients with COPD somewhat disagreed/strongly disagreed that smoking is the cause of most cases of COPD. We found that the smokers feared COPD more than the ex- and never-smokers, but the figures were however low (5.1 vs .…”
Section: Discussionsupporting
confidence: 52%
“… 16 In a multinational study including centers from the Europe and the United States, 24% of the COPD patients reported that they had not undergone a spirometry test. 17 As can be seen from different population examples, PFTs are not always incorporated in the diagnosis and management of COPD in several parts of the world. The present study showed that spirometry was frequently overlooked in clinical practice in Turkey and that the physicians had problems in interpreting the results when it was performed.…”
Section: Discussionmentioning
confidence: 99%
“…A multinational study conducted in 12 countries also revealed high awareness among treating physicians about COPD management. [1214] The study also showed that for the treatment of COPD (GOLD Stage B), 38% general physicians and 67% of pulmonologists prescribed treatment as per guidelines. [14] In this study, we found that 34.8% of pulmonologists were prescribing treatment as per guidelines, and the patients of GOLD Stage B were being over-treated with ICSs.…”
Section: Discussionmentioning
confidence: 99%
“…[11] However, similar to our study, 86% of physicians were using spirometry for the diagnosis of COPD in a multinational study conducted in 12 countries. [12] GOLD presently recommends the use of spirometry, which is a reproducible test, for diagnosis and assessment of severity of COPD. The postbronchodilator spirometry values are being used to establish the GOLD stage of the disease and prescribe treatment accordingly.…”
Section: Discussionmentioning
confidence: 99%